2022
DOI: 10.1159/000525298
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain in Children during the COVID-19 Pandemic and the Protective Effect of Lifestyle Intervention in Children with Obesity

Abstract: Introduction: School closures due to the COVID-19 pandemic affect children’s daily structure, mealtimes, physical activity and sleeping habits, possibly exacerbating weight gain, particularly in vulnerable children with overweight and obesity. This study aims to evaluate both perceived and objectively measured weight gain in children in the Netherlands during the COVID-19 pandemic and the effect of prior lifestyle intervention. Methods: 150 children of the Children, Obesity and Lifestyle during COVID-19 (COLC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
1
1
0
1
Order By: Relevance
“…In this representative online survey among parents in Germany, we were interested to determine the impact of repeated lockdowns and episodes of closure of educational institutions, home-schooling and social distancing on lifestyle, body weight, and mental health of children and adolescents during 2 years of the COVID-19 pandemic. With regard to a self-reported increase in body weight during the COVID-19 pandemic above what would have been expected based on physical development [14], our results are in line with other studies from Germany [7, 8, 15], the USA [9, 1618], Italy [10], the Netherlands [19], Austria [20], China [21], and Korea [22], which have also shown that body weight has increased disproportionately in children and adolescents since the beginning of the COVID-19 pandemic. In addition, the risk for weight gain during the COVID-19 pandemic was higher for children from low-income families [16] and for children with preexisting overweight or obesity [7, 17], a finding that was also observed in our survey.…”
Section: Discussionsupporting
confidence: 92%
“…In this representative online survey among parents in Germany, we were interested to determine the impact of repeated lockdowns and episodes of closure of educational institutions, home-schooling and social distancing on lifestyle, body weight, and mental health of children and adolescents during 2 years of the COVID-19 pandemic. With regard to a self-reported increase in body weight during the COVID-19 pandemic above what would have been expected based on physical development [14], our results are in line with other studies from Germany [7, 8, 15], the USA [9, 1618], Italy [10], the Netherlands [19], Austria [20], China [21], and Korea [22], which have also shown that body weight has increased disproportionately in children and adolescents since the beginning of the COVID-19 pandemic. In addition, the risk for weight gain during the COVID-19 pandemic was higher for children from low-income families [16] and for children with preexisting overweight or obesity [7, 17], a finding that was also observed in our survey.…”
Section: Discussionsupporting
confidence: 92%
“…Esse fator pode ser relacionado diretamente com a qualidade alimentar, em que comidas mais baratas e rápidas eram preferíveis, já que houve um maior consumo de fast-food (Woo et al 2022). O risco de desenvolvimento de outras comorbidades, como doença hepática gordurosa não alcoólica, diabetes tipo 2, problemas psicossociais e do risco de infecção por Covid-19 foi abordado por Lubrecht et al (2022) e Shalitin et al (2022).…”
Section: Discussionunclassified
“…Notably, unhealthy eating behaviors that started in the pandemic seemed more difficult to reverse and sometimes remained, whereas the positive effects diminished. This suggests that the abovementioned unhealthy alterations in eating patterns due to the pandemic might have lasting implications for the weight of children and adolescents in the future and mainly in the children with overweight or obesity [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%